Locked Superior Dislocation of the Acromioclavicular Joint. (18th December 2013) - Elamin, Salma Eltoum; Sinha, Apurv; Webb, Mark
Abstract : Acromioclavicular (AC) joint injuries account for approximately 3–5% of shoulder girdle injuries (Rockwood et al., 1998). Depending on severity of injury and direction of displacement these are classified using Rockwood classification system for AC joint dislocation. We present an unusual case presenting with locked superior dislocation of the AC joint highlighting the presentation and subsequent successful surgical management of such case. To our knowledge this has not been reported previously in literature.